Faktor-Faktor yang Mempengaruhi Perilaku Dosen STAI Auliaurrasyidin Tembilahan dalam Memilih Produk Bank Syariah - Siti Zariah (STAI Auliaurrasyidin Tembilahan, 2021)
This research was motivated by The sharia economy is now entering the world of education, in addition to banks and other non-bank financial institutions that are busy adding the